Thoracolithiasis Mimicking a Pleural Plaque in a Patient with a History of Asbestos Exposure: A Case Report - Yoon Ki Cha; Jeung Sook Kim; Jin-Ho Choi; Kang Min Han (대한영상의학회지, 2017)
A freely mobile calcified or noncalcified nodule in the pleural cavity, known as thoracolithiasis, is quite rare. There are several reports of CT findings of thoracolithiasis, but there is no report of thoracolithiasis mistakenly considered as a pleural plaque in a patient with a history of asbestos exposure. We report a case of a 61-year-old man with a mobile pleural stone thoracoscopically confirmed as thoracolithiasis and which was regarded as a pleural plaque on CT scan in a patient with a history of asbestos exposure.